Evaluation of antihyperglyicemic potential of Pfaffia glomerata (Spreng.) Pedersen (Amaranthaceae) - Sanches, Neviton Rogerio (2008)
The roots of Pfaffia glomerata (Spreng.) Pedersen (Amaranthaceae), commonly known as Brazilian ginseng, are used in folk medicine as a tonic and as an aphrodisiac and antidiabetic medicine. The methanolic extract and its fractions obtained from roots were used to evaluate their antihyperglycemic potential in male Wistar rats. While the methanolic extract yielded four fractions, the butanolic extract had larger antihyperglycemic potential, starting from 50 mg/kg. No activity was shown by its fractionation. The β-ecdisone identified in the butanolic extract is not related with the antihyperglycemic effect